INTERDISCIPLINARY SOCIOLOGICAL APPROACH USING THE QUESTIONNAIRE RESEARCH METHOD REGARDING THE LEARNING OF BASKETBALL IN FIFTH GRADE PUPILS (Fiep Bulletin - online, 2014)
The questionnaire-type inquiry was used aiming to analyze the correct and pertinent answers of the specialists dealing with teaching basketball during the physical education lessons, in Romania. The questionnaire represents a logical and psychological succession of written questions, or images, serving as stimuli, related to the hypotheses of the research, which, administered by the researchers, or selfadministered, determine a verbal or nonverbal response from the subject, which is subsequently recorded in writing. For this sociological research we elaborated a questionnaire comprising 12 questions that would allow us to know the real facts on the learning of basketball at the secondary school level. The questionnaire was sent to a total of 58 specialists, who work in schools from Bac?u, One?ti, Ia?i, Boto?ani, Foc?ani, and Suceava (Romania). The responses were correlated to theoretical issues that emerged from the study of national and international literature. The questionnaire was applied between September 2012 and April 2013.
Keywords: interdisciplinary; sociological approach; basketball; 5th grade